Relationship Between Mothers Knowledge Level and the Timing of Providing Complementary Foods to Infants Aged 6-24 Months in Langa Community Health Center Work Area, Ngada Regency - Dika, Maria Faustina Veren; Hutasoit, Regina Marvina; Adang, Gottfrieda P. Taeng-Ob; Wardani, Nimas Prita R. K. (Jurnal Biologi Tropis, 2026)
Inappropriate timing of complementary feeding causes nutritional problems and increases the likelihood of malnutrition in the region. Mothers' understanding of complementary feeding is crucial in determining when and how it is introduced. This study aims to explore the relationship between maternal knowledge and the appropriate timing of complementary feeding in the area served by the Langa Community Health Center. This study included a correlational analysis with a cross-sectional approach. Data analysis in this study was conducted using univariate and bivariate approaches (Chi-Square test). The results of the analysis showed that the timing of introducing complementary feeding at six months of age was 64.1%. Meanwhile, maternal knowledge was assessed as being in the good range at 48.5%. The bivariate analysis showed a significant relationship between maternal knowledge level, good or bad, and the timing of introducing complementary feeding. The conclusion is that there is a significant relationship between maternal knowledge level and the timing of introducing complementary feeding in infants aged 6 to 24 months in the Langa Community Health Center area, Ngada Regency.